Return to Nim's island [videorecording (DVD)] - Irwin, Bindi, 1998-; Wallace, Toby; Lillard, Matthew, 1970-; Waters, John Russell, 1948-; Maher, Brendan (Walden Media ; Manufactured and distributed by ARC Entertainment, LLC, 2013)
Nim is the precocious daughter of scientist father Jack. Nim, a bit older now, still has a gift to be "one with nature" and her amazing animal friends. But now that developers and poachers threaten her island, she and her dad must fight to preserve their pristine home and its abundant wildlife.